Statistical Analysis of Yttrium-Doped ZnO Nanoparticles for Gas Sensing Applications - Kumar, Satender; Nehra, Ankur (The Nucleus, 2025)
Yttrium-doped ZnO (YZ) thin films were synthesized using sol-gel spin coating technique on planar glass substrates. Their optical and electrical properties were analyzed to assess their potential for O₂ gas detection. XRD analysis confirmed a hexagonal wurtzite crystal structure, while FE-SEM images revealed a network of spherical nanoparticles. Optical transmission spectra showed that increasing Y-dopant concentration widened the bandgap from 3.27 eV to 3.30 eV. Electrical measurements indicated that YZ3 exhibited highest conductivity. Gas sensing performance was evaluated for YZ2 and YZ4 at an O₂ flow rate of 450 sccm and an operating temperature of 70°C. Among them, YZ4 demonstrated the highest response, reaching a value of 1, with a fast response time of 2 seconds and a recovery time of 4 seconds. Statistical analysis suggests that YZ thin films hold promise for efficient gas sensing at lower operating temperatures.